OBLIGASI SYARI'AH (Analisi Normatif, Praksis dan Komparatif Perbankan Konvensional dan Perbankan Syariah) - Moh Sholeh (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2013)
Obligation represent one of the monetary instrument which enough draw to investor circle in capital market and or to company in getting fund for the development of company. Growth of obligation product in Indonesia relative still compared to slowgoing growth of share product. Since 1990, noted more than 23 company publishing obligation and only experiencing of growth become 120 publisher of obligation until September month; moon 2003 with value more than 45 triliun rupiah. Obligation represent letter owe from a[n company or institute which selling to investor to get fresh fund. Investor will get return in the form of certain rate of interest storey; level very depended varying strength of its publisher business. This rate of interest can be paid fied or have ladder. In money market which have expanded better form and obligation type can reach to flg even tens.